Numerical Modelling of Milne Fiord Future ... - Bonneau, Jérémie; Mueller, Derek; Laval, Bernard E (Federated Research Data Repository / dépôt fédéré de données de recherche, 2024)
This dataset contains the setup, input and output of seven three dimensional numerical simulations of Milne Fiord (Nunavut, Canada), built using MITgcm. These simulations were carried out to investigate the impact of ice structures (ice shelf, glacier tongue, tidewater glacier) on the ocean circulation in Milne Fiord, and to quantify the impact of future ocean warming on the retreat of Milne Glacier. These simulations are variation of the baseline simulation: "Numerical Modelling of Milne Fiord 2011-2019; https://doi.org/10.20383/103.0887". This dataset contains different simulations with the same setup, but with ice configurations and water temperature representative of the future in the fjord. ...